2007
DOI: 10.1042/bj20070040
|View full text |Cite
|
Sign up to set email alerts
|

A reversible form of lysine acetylation in the ER and Golgi lumen controls the molecular stabilization of BACE1

Abstract: The lipid second messenger ceramide regulates the rate of beta cleavage of the Alzheimer's disease APP (amyloid precursor protein) by affecting the molecular stability of the beta secretase BACE1 (beta-site APP cleaving enzyme 1). Such an event is stimulated in the brain by the normal process of aging, and is under the control of the general aging programme mediated by the insulin-like growth factor 1 receptor. In the present study we report that BACE1 is acetylated on seven lysine residues of the N-terminal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
174
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(178 citation statements)
references
References 49 publications
4
174
0
Order By: Relevance
“…For example, reversible acetylation in the luminal domain of BACE1 regulates its stability as well as exit from the ER (20,57). Moreover, phosphorylation regulates the fate of BACE1 endocytosed from the cell surface; whereas phosphorylated BACE1 is transported from the endosomes to the TGN, non-phosphorylated BACE1 is directly recycled to the cell surface (18,29).…”
Section: Bace1 Is S-palmitoylated At 4 Cysteine Residues-previ-mentioning
confidence: 99%
“…For example, reversible acetylation in the luminal domain of BACE1 regulates its stability as well as exit from the ER (20,57). Moreover, phosphorylation regulates the fate of BACE1 endocytosed from the cell surface; whereas phosphorylated BACE1 is transported from the endosomes to the TGN, non-phosphorylated BACE1 is directly recycled to the cell surface (18,29).…”
Section: Bace1 Is S-palmitoylated At 4 Cysteine Residues-previ-mentioning
confidence: 99%
“…BACE1 belongs to the pepsin family and has a close homolog BACE2 (7). BACE1 is synthesized as a proenzyme in the endoplasmic reticulum, where it is acetylated (9) and glycosylated (10). During Golgi transit, BACE1 becomes deacetylated and mature N-glycosylated.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Our group has shown that the TrkA to p75 NTR switch that occurs downstream of IGF1-R is responsible for the molecular stabilization of BACE1 and the increased generation of Aβ that accompanies aging [6,7,8,32]. The strict requirement for p75 NTR is proved by the fact that animals expressing a truncated version of the receptor (p75 NTRExonIII−/− ; lacking the ligand binding domain) were able to activate neither ceramide nor Aβ generation [8].…”
Section: Discussionmentioning
confidence: 99%
“…The TrkA to p75 NTR switch is responsible for an age-dependent activation of neutral sphingomyelinase (nSMase), the enzyme that converts cell-surface sphingomyelin (SM) into the second messenger ceramide. Ceramide, in turn, is responsible for the molecular stabilization of the β-site APP cleaving enzyme (BACE1), and for the increased β cleavage of the Alzheimer's disease (AD) amyloid precursor protein (APP) that accompanies aging [6,7,8,32]. These results are particularly important because aging is the single most important risk-factor for late-onset AD, which represents the most common form of dementia in the world [15,39].…”
Section: Disclosure Statementmentioning
confidence: 99%
See 1 more Smart Citation